The oral CDK9 inhibitor voruciclib combined with venetoclax for patients with relapsed/refractory acute myeloid leukemia - Yesid Alvarado-Valero; Rachel J. Cook; Shira N. Dinner; Michael Keng; Kebede H. Begna; Nathalie Javidi-Sharifi; Sameem Abedin; Monzr M. Al Malki; Vijaya Raj Bhatt; Prabhu Rajagopalan; Min Tang; Sandra E. Wiley; et al. (Blood Neoplasia)
Abstract: The antiapoptotic protein myeloid cell leukemia 1 (Mcl-1) promotes cell survival in acute myeloid leukemia (AML), and its overexpression is associated with resistance to venetoclax. Voruciclib, an oral cyclin-dependent kinase 9 inhibitor, indirectly decreases Mcl-1 protein expression and has synergistic activity with venetoclax in AML preclinical models. We hypothesized that voruciclib in combination with venetoclax would induce responses in patients with AML with disease progression after venetoclax therapy. This dose-escalation study evaluated voruciclib administered on days 1 to 14 of 28-day cycles with venetoclax daily. The study enrolled 41 adult patients with AML after failure of previous standard therapies. Patients had a median of 2 (range, 1-7) previous lines of therapy, 19 patients (46%) had ≥3 previous lines of therapy, and 39 (95%) had previous venetoclax. No dose-limiting toxicities were reported in 7 dose levels evaluated. The most common adverse events were nausea (34%), febrile neutropenia (32%), diarrhea (22%), dyspnea (22%), hypokalemia (22%), and thrombocytopenia (22%). Antileukemic activity was observed in 10 (24%) patients, including 3 with complete marrow remission and 7 with stable disease lasting ≥3 months. We observed a rebound of circulating blasts during the 14 days of single-agent venetoclax dosing in 40% of evaluable patients. Mcl-1 protein expression and RNA polymerase II Ser-2 phosphorylation decreased on voruciclib. Overall, the combination of voruciclib with venetoclax was tolerable in patients with relapsed/refractory AML, had antileukemic activity, and showed on-target effects in heavily pretreated patients with disease progression after venetoclax. This trial was registered at www.ClinicalTrials.gov as #NCT03547115.